Avizandum Legislation on International Private Law - Crawford, Elizabeth (Avizandum Statutes Ser., 2020)
This volume provides ready access to a wide-ranging selection of materials on those areas of private law in which a foreign element may arise. It includes UK and Scottish statutes and statutory instruments, EU materials and International Conventions.